Cyanotic congenital heart disease following fertility treatments in the United States from 2011 to 2014. Issue 11 (16th November 2017) - Shamshirsaz, Alireza A; Bateni, Zhoobin H; Sangi-haghpeykar, Haleh; Arian, Sara E; Erfani, Hadi; Shamshirsaz, Amir A; Abuhamad, Alfred; Fox, Karin A; Ramin, Susan M; Moaddab, Amirhossein; Maskatia, Shiraz A; Salmanian, Bahram; et al.
Abstract : Objective: To examine the risk for cyanotic congenital heart diseases (CCHDs) among live births in the USA, resulting from various forms of infertility treatments. Methods: This study is a cross-sectional analysis of live births in the USA from 2011 to 2014. Infertility treatments are categorised into two of the following groups on birth certificates: assisted reproductive technology (ART) fertility treatment (surgical egg removal; eg, in vitro fertilisation and gamete intrafallopian transfer) and non-ART fertility treatment (eg, medical treatment and intrauterine insemination). We compared the risk for CCHD in ART and non-ART fertility treatment groups with those infants whose mothers received no documented fertility treatment and were naturally conceived (NC). Results: Among 14 242 267 live births from 2011 to 2014, a total of 101 494 live births were in the ART and 81 242 resulted from non-ART fertility treatments. CCHD prevalence in ART, non-ART and NC groups were 393/100 892 (0.39%), 210/80 884 (0.26%) and 10 749/14 020 749 (0.08%), respectively. As compared with naturally conceiving infants, risk for CCHD was significantly higher among infants born in ART (adjusted relative risk (aRR) 2.4, 95% CI 2.1 to 2.7) and non-ART fertility treatment groups (aRR 1.9, 95% CI 1.6 to 2.2). Absolute risk increase in CCHD due to ART and non-ART treatments were 0.03% and 0.02%,  respectively. A similar pattern was observed when the analysis was restricted to twins, newborns with birth weights under 1500 g and gestational age of less than 32 weeks. Conclusions: Our findings suggest an increased risk for CCHD in infants conceived after all types of infertility treatment.